Mechanisms and Environmental Determinants of Food Allergies: An Integrative Review - Gbenga-Olusanya, Oluwayomi; Kpai, Tonubari; Ayegboyin, Olusola Adebayo; Oghenetega, Onome Bright (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2025)
IgE-mediated food allergy is a growing global health concern characterized by a dysregulated immune response to dietary proteins, causing symptoms from urticaria to anaphylaxis. This review critically examines current evidence on the immunopathology, diagnosis, and management of IgE-mediated food allergy, aiming to identify gaps and priorities for future research. A comprehensive search of PubMed, Scopus, and Web of Science was performed up to April 2025 using terms related to food allergy, including pathophysiology, epidemiology, diagnosis, and treatment. English-language original and review articles were selected to provide a broad overview, and data were synthesized narratively to summarize key findings and emerging trends globally. Prevalence has surged over the past two decades, affecting up to 10% of populations in Western nations, with rising cases in non-Western regions linked to urbanization and dietary changes. The pathophysiology involves failure of oral tolerance, TH2 polarization, and IgE-mediated activation of mast cells and basophils, which upon re-exposure, release histamine, leukotrienes, and cytokines, driving acute inflammation. Key allergens include peanuts, milk, eggs, and shellfish, with proteins like Ara h 2 (peanut) and tropomyosin (shellfish) resisting digestion, enhancing immunogenicity. Contributing factors encompass genetic predisposition, epithelial barrier defects (e.g., filaggrin mutations in atopic dermatitis), and altered gut microbiota, which disrupt regulatory T-cell (Treg) function critical for immune tolerance. Current management relies on allergen avoidance and emergency epinephrine, while adjunct therapies like antihistamines and corticosteroids address mild symptoms. Despite advances, diagnostic challenges persist, particularly in resource-limited settings, compounded by misdiagnosis and inadequate access to care. Emerging research highlights microbiota modulation, epicutaneous immunotherapy, and Treg induction as promising strategies to restore tolerance. Future directions emphasize the need for biomarkers, precision therapies, and elucidating interactions between genetic, environmental, and immunological drivers to mitigate the global burden of food allergy.